Carbon felt for flow battery as well as preparation method and application of carbon felt
By performing activation, impregnation, reduction and carbon nanotube growth of carbon felts with flow batteries, the problems of low specific surface area and poor electrochemical activity of the carbon felts are solved, and the electrochemical performance and cycle life of the flow batteries are significantly improved. .
Patent Information
- Application Number
- CN202411851081.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-18
AI Technical Summary
The existing carbon felts for flow batteries have problems with low specific surface area and poor electrochemical activity, which leads to poor electrochemical performance of flow batteries, including high polarization, low energy efficiency and short cycle life.
The carbon felt was activated by concentrated nitric acid solution, followed by impregnation with a low-concentration transition metal salt solution and reduction treatment in the presence of hydrogen. Next, the carbon nanotubes were grown by CVD method in the presence of organic hydrocarbon gas, and purified under a halogen atmosphere.
The Coulomb efficiency, voltage efficiency and energy efficiency of the flow battery are significantly improved, and the cycling performance of the battery is extended.
Smart Images

Figure CN119481120A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon felt for a liquid flow battery and a preparation method and application thereof, belonging to the technical field of production of organic energy storage liquid flow batteries. Background Art
[0002] As global energy demand continues to increase, traditional fossil energy resources are becoming increasingly depleted, and their exploitation and use have increasingly significant negative impacts on the environment. Therefore, the development of sustainable, clean, and efficient energy storage technology has become an important direction of scientific research today.
[0003] As a storage technology with high energy density, long life, intrinsic safety and flexibility, flow battery has broad application prospects in the storage of renewable energy and distributed energy systems.
[0004] One of the core components of flow batteries is the electrode, and carbon felt, as a commonly used electrode material, has good conductivity, corrosion resistance and a certain specific surface area, so it is widely used in flow batteries. However, existing commercial carbon felt electrodes generally have problems such as low specific surface area and poor electrochemical activity, which limit the electrochemical performance of flow batteries, such as high battery polarization, low energy efficiency, and short cycle life.
[0005] At present, there are two main methods to increase the specific surface area of carbon felt: one is to form a pore structure on the carbon fiber surface through chemical etching of the carbon fiber surface to increase the specific surface area; the other is to introduce other carbon materials on the carbon fiber surface through vapor deposition, polymer carbonization and other methods to form a composite structure.
[0006] However, these methods have some problems. For example, chemical etching on the carbon fiber surface may destroy the main structure of the carbon fiber and reduce the fiber strength. Carbon materials introduced only by vapor deposition and other methods will contain some impurity carbon. In addition, the bonding force between the introduced carbon materials and the carbon fiber body is weak and they are easy to fall off after long-term use, affecting the electrode performance.
[0007] A Chinese patent (publication number CN 115881981 A) discloses a method for preparing carbon felt for redox flow battery, which is characterized by comprising the following steps: (1) using mesophase pitch carbon fiber as raw material, preparing carbon felt by needle punching method; (2) using hydrogen as etchant and argon as regulating gas to etch the carbon felt; (3) using nickel nitrate aqueous solution to immerse the etched carbon felt, and then drying; (4) using nickel nitrate as catalyst and small molecule hydrocarbon compound as reaction carbon source gas to generate carbon nanotubes on the surface of carbon felt; (5) graphitizing the carbon felt; (6) soaking the graphitized carbon felt with concentrated nitric acid, then washing with water, and drying to obtain carbon felt for redox flow battery. However, this method has the influence of some additives in the original carbon felt, which is not conducive to its hydrogen etching, resulting in the easy fall-off of carbon nanotubes in the flow battery, which reduces the energy efficiency of the flow battery; the carbon source gas has weak reducing property, resulting in slow growth of carbon tubes; the purification process is cumbersome and time-consuming. Summary of the invention
[0008] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing carbon felt for liquid flow batteries, wherein the carbon felt is activated by a concentrated nitric acid solution, then impregnated with a low concentration transition metal salt solution, and then reduced, and carbon nanotubes are grown on the surface of the carbon felt in the presence of an organic hydrocarbon gas, followed by purification. The method is simple, easy, low-cost, highly controllable, and can prepare carbon felt materials with a high comparative area. When used to prepare liquid flow batteries, the coulombic efficiency, voltage efficiency and energy efficiency of the liquid flow batteries can be significantly improved, and the battery cycle performance is better.
[0009] In order to achieve the above object, the first aspect of the present invention provides a method for preparing carbon felt for a flow battery, the method comprising the following steps: (1) activating the carbon felt in a concentrated nitric acid solution to obtain carbon felt I; the carbon felt is obtained by carbonizing polyacrylonitrile-based fibers; (2) immersing the carbon felt I in a transition metal salt solution, and then drying it to obtain carbon felt II; (3) subjecting the carbon felt II to a reduction treatment in the presence of hydrogen to obtain carbon felt III; (4) growing carbon nanotubes on the surface of carbon felt III by CVD method to obtain carbon felt IV; (5) The carbon felt IV is purified under a halogen atmosphere to obtain carbon felt for liquid flow battery.
[0010] The innovation of the present invention lies in that the carbon felt is pre-treated by the activation-coordination-in-situ reduction method, and then carbon nanotubes are grown on the surface of the carbon felt by the CVD method. The carbon felt is first activated by concentrated nitric acid to generate more active sites on the surface of the carbon felt, making it more conducive to the attachment of subsequent catalyst particles and making it difficult for the generated carbon nanotubes to fall off. In addition, concentrated nitric acid can also remove additives remaining on the surface of the carbon felt during the preparation of the carbon felt, and polar functional groups such as hydroxyl and carboxyl are introduced after the activation treatment to improve the wettability of the carbon felt. Then, hydrogen is used to reduce the catalyst so that the catalyst is evenly loaded on the carbon felt, making the grown carbon nanotubes more uniform and having a high growth rate, thereby further improving the specific surface area of the carbon felt.
[0011] The carbon felt obtained by carbonizing polyacrylonitrile-based fibers has high electrochemical activity and good corrosion resistance, and is more stable in the liquid flow battery system; this carbon felt has a large market share and mature technology. However, this type of carbon felt has a large number of unsaturated carbon atoms on the surface, and there are also some metal impurities and additives. In the liquid flow battery system, it may consume electrolytes, cause side reactions, and reduce conductivity; its surface hydrophilicity is poor, resulting in a small contact area with the electrolyte and poor conductivity. The method provided by the present invention can effectively remove additives and metals on the surface of carbon felt, purify carbon felt, and increase the carbon nano-specific surface area. When used in liquid flow batteries, it can significantly improve the coulombic efficiency, voltage efficiency, and energy efficiency of the liquid flow battery, and the battery cycle performance is better.
[0012] In a preferred solution, the activation treatment conditions are: temperature of 50-70°C and time of 20-40 minutes. The inventors found that under this preferred condition, the surface of the carbon felt can be effectively protected from being damaged and impurities can be removed.
[0013] In a preferred embodiment, the transition metal salt solution is selected from at least one of a cobalt salt solution, an iron salt solution and a nickel salt solution.
[0014] In a preferred embodiment, the concentration of the transition metal salt is 0.05-0.1 wt %. The inventors found that too low a transition metal salt concentration would result in insufficient adhesion of the transition metal salt, resulting in no significant improvement in the performance of the carbon felt; too high a salt concentration would result in the carbon felt being covered with a large amount of carbon nanotubes, thus losing its own performance advantages.
[0015] It should be noted that the present invention has no special requirements on the amount of the transition metal salt solution used, and the amount of the transition metal salt solution used can be such that the carbon felt I is completely immersed in the transition metal salt solution.
[0016] In a more preferred embodiment, the transition metal salt solution is a nickel nitrate solution.
[0017] In a preferred embodiment, the immersion is carried out under ultrasonic conditions, and the ultrasonic conditions are: power of 800-1200 W and time of 5-20 min.
[0018] In a preferred embodiment, step (3), step (4) and step (5) are all carried out in an inert gas.
[0019] In a preferred embodiment, the reduction treatment conditions are as follows: hydrogen flow rate is 150-250 ml / min, inert gas flow rate is 150-250 ml / min, temperature is 600-700° C., and time is 3-10 min.
[0020] In a preferred embodiment, the conditions of the CVD method are: growing carbon nanotubes on the surface of carbon felt III in the presence of an organic hydrocarbon gas, with a flow rate of the organic hydrocarbon gas of 150-300 ml / min, a flow rate of the inert gas of 150-250 ml / min, a temperature of the CVD method of 600-700°C, and a time of 5-30 min.
[0021] In a preferred embodiment, the organic hydrocarbon gas is selected from at least one of propylene, ethylene, acetylene and methane.
[0022] In a preferred embodiment, the halogen atmosphere is selected from at least one of hydrogen chloride, chlorine and freon.
[0023] The conditions for the purification treatment in the preferred scheme are: the flow ratio of the inert gas and the halogen atmosphere is (1-20):1, the temperature is 900-1500°C, and the time is 1-3h.
[0024] The present invention provides a method for preparing a carbon felt for a liquid flow battery, which specifically comprises the following steps: S1: activating the untreated carbon felt in a concentrated nitric acid solution at a temperature of 50-70°C for 20-40 minutes, washing with water until the pH value is 6-8, and drying at 120-200°C for 1.5-3 hours to obtain carbon felt I; S2: immersing the carbon felt I in a transition metal salt solution with a concentration of 0.05-0.1 wt%, placing it in an ultrasonic cleaner with a power of 800-1200 W for 5-20 min, and continuing to dry it at 120-200° C. for 1.5-3 h to obtain carbon felt II; S3: placing carbon felt II in a tubular furnace, setting the inert gas flow rate to 150-250 ml / min, heating to 600-700°C, introducing hydrogen, setting the hydrogen flow rate to 150-250 ml / min, and keeping the temperature for 3-10 minutes to obtain carbon felt III; S4: stop introducing hydrogen, set the flow rate of organic hydrocarbon gas to 150-300 ml / min, the flow rate of inert gas to 150-250 ml / min, keep warm at 600-700° C. for 5-30 min, and grow carbon nanotubes on the surface of carbon felt III by CVD method to obtain carbon felt IV; S5: Stop introducing the organic hydrocarbon gas, introduce the halogen gas, purify the carbon felt IV under the halogen gas at a temperature of 900-1500° C. for 1-3 hours, and obtain the carbon felt for liquid flow battery after cooling to room temperature.
[0025] The present invention also provides a carbon felt for a liquid flow battery prepared by the above method. The carbon felt for a liquid flow battery has a large specific surface area, and the carbon nanotubes are evenly distributed and are not easy to fall off after long-term use.
[0026] The present invention also provides the application of the carbon felt for liquid flow battery in the liquid flow battery. When the carbon felt is used to prepare the liquid flow battery, more reaction channels and reaction sites can be provided, thereby significantly improving the coulombic efficiency of the liquid flow battery.
[0027] Compared with the prior art, the present invention has at least the following advantages: (1) The method provided by the present invention uses concentrated nitric acid to activate the carbon felt, so that more active sites are generated on the surface of the carbon felt, which is more conducive to the attachment of subsequent catalyst particles and makes the generated carbon nanotubes less likely to fall off; and polar functional groups such as hydroxyl and carboxyl groups can be introduced through activation to improve the wettability of the carbon felt, thereby increasing its specific surface area.
[0028] (2) The purification method of the present invention uses a halogen atmosphere to remove impure metals on the surface of the carbon felt, which is more time-saving and greatly reduces costs compared to traditional high-temperature purification methods.
[0029] (3) The present invention adopts the activation-coordination-in-situ reduction method to pre-treat the carbon felt, and then adopts chemical vapor deposition to grow carbon nanotubes so that the generated carbon nanotubes are not easy to fall off. At the same time, a three-dimensional conductive skeleton is constructed, which greatly increases the specific surface area of the carbon felt, can provide more reaction channels and reaction sites, significantly improves the coulombic efficiency of the liquid flow battery, and the battery has better cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a scanning electron microscope image of untreated carbon felt I; Figure 2 This is a scanning electron microscope image of the carbon felt for flow battery prepared in Example 1; Figure 2 The left picture in the figure is a scanning electron microscope picture at 200 times; Figure 2 The right picture in the figure is a scanning electron microscope picture at 5000 times; Figure 3This is a transmission electron microscope image of carbon nanotubes of the carbon felt for liquid flow battery prepared in Example 1; Figure 4 The carbon felt provided in Examples 1 to 4 was prepared into a battery and the untreated carbon felt I was prepared into a battery at a current density of 160 mA•cm -2 Schematic diagram of the Coulombic efficiency under .
[0031] Figure 5 The carbon felt provided in Examples 1 to 5 and Comparative Examples 1 to 4 was prepared into a battery with a battery density of 160 mA•cm -2 Schematic diagram of energy efficiency. DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] In the present invention, room temperature refers to 25±2°C.
[0034] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by professionals in this field without creative work still belong to the protection scope of the present invention.
[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0036] Example 1 Untreated carbon felt I: It is made of polyacrylonitrile-based fiber by needle punching method, with a size of 5×5×1 cm, and the brand is PAN-based cured carbon felt. The manufacturer purchased is Liaoning Jingu Carbon Materials Co., Ltd.
[0037] S1: The untreated carbon felt was activated in a concentrated nitric acid solution (68 wt%) at 60°C for 30 min, washed with water until the pH value was 7, and then dried at 150°C for 2 h to obtain carbon felt I; S2: The carbon felt I is immersed in a nickel nitrate solution with a concentration of 0.1 wt%, and then placed in an ultrasonic cleaner with a power of 1000 W for 15 min, and then dried in an oven at 150° C. for 2 h to obtain carbon felt II; S3: placing carbon felt II in a tubular furnace, setting the nitrogen flow rate to 200 ml / min, heating to 640°C, introducing hydrogen, setting the hydrogen flow rate to 150 ml / min, and keeping the temperature for 5 minutes to obtain carbon felt III; S4: stop introducing hydrogen, set the flow rate of propylene to 150 ml / min, the flow rate of nitrogen to 250 ml / min, keep warm at 640° C. for 15 min, and grow carbon nanotubes on the surface of carbon felt III by CVD method to obtain carbon felt IV; S5: Stop introducing propylene, introduce hydrogen chloride gas, set the hydrogen chloride flow rate to 200 ml / min, the nitrogen flow rate to 250 ml / min, purify the carbon felt IV at 1100° C. for 1 h, cool to room temperature, and obtain carbon felt for liquid flow battery.
[0038] Figure 1 This is a scanning electron microscope image of untreated carbon felt I. It can be seen from the image that the surface of the carbon felt is smooth and not suitable for the attachment of carbon nanotubes.
[0039] Figure 2 This is a scanning electron microscope image of the carbon felt for liquid flow battery prepared in this example. It can be seen from the image that a large number of carbon nanotubes are attached to the surface of the carbon felt.
[0040] Figure 3 This is a transmission electron microscope image of the carbon nanotubes of the carbon felt for liquid flow battery prepared in Example 1. It can be seen from the image that the carbon nanotubes on the surface of the prepared carbon felt have a small diameter.
[0041] Example 2 The untreated carbon felt is the same as that in Example 1.
[0042] S1: The untreated carbon felt was activated in a concentrated nitric acid solution (68 wt%) at 60°C for 30 min, washed with water until the pH value was 7, and then dried at 150°C for 2 h to obtain carbon felt I; S2: The carbon felt I was immersed in a 0.1 wt% ferric nitrate solution, and then placed in an ultrasonic cleaner with a power of 1000 W for 15 min, and then dried in an oven at 150° C. for 2 h to obtain carbon felt II; S3: placing carbon felt II in a tubular furnace, setting the nitrogen flow rate to 200 ml / min, heating to 640°C, introducing hydrogen, setting the hydrogen flow rate to 150 ml / min, and keeping the temperature for 5 minutes to obtain carbon felt III; S4: stop introducing hydrogen, set the flow rate of propylene to 150 ml / min, the flow rate of nitrogen to 250 ml / min, keep warm at 640° C. for 15 min, and grow carbon nanotubes on the surface of carbon felt III by CVD method to obtain carbon felt IV; S5: Stop introducing propylene, introduce hydrogen chloride gas, set the hydrogen chloride flow rate to 200 ml / min, the nitrogen flow rate to 250 ml / min, purify the carbon felt IV at 1100° C. for 1 h, cool to room temperature, and obtain carbon felt for liquid flow battery.
[0043] Example 3 The untreated carbon felt is the same as that in Example 1.
[0044] S1: The untreated carbon felt was activated in a concentrated nitric acid solution (68 wt%) at 60°C for 30 min, washed with water until the pH value was 7, and then dried at 150°C for 2 h to obtain carbon felt I; S2: The carbon felt I is immersed in a cobalt nitrate solution with a concentration of 0.1 wt%, and then placed in an ultrasonic cleaner with a power of 1000 W for 15 min, and then dried in an oven at 150° C. for 2 h to obtain carbon felt II; S3: placing carbon felt II in a tubular furnace, setting the nitrogen flow rate to 200 ml / min, heating to 640°C, introducing hydrogen, setting the hydrogen flow rate to 150 ml / min, and keeping the temperature for 5 minutes to obtain carbon felt III; S4: stop introducing hydrogen, set the flow rate of propylene to 150 ml / min, the flow rate of nitrogen to 250 ml / min, keep warm at 640° C. for 15 min, and grow carbon nanotubes on the surface of carbon felt III by CVD method to obtain carbon felt IV; S5: Stop introducing propylene, introduce hydrogen chloride gas, set the hydrogen chloride flow rate to 200 ml / min, the nitrogen flow rate to 250 ml / min, purify the carbon felt IV at 1100° C. for 1 h, cool to room temperature, and obtain carbon felt for liquid flow battery.
[0045] Example 4 The untreated carbon felt is the same as that in Example 1.
[0046] S1: The untreated carbon felt was activated in a concentrated nitric acid solution (68 wt%) at 70°C for 30 min, washed with water until the pH value was 7, and then dried at 150°C for 2 h to obtain carbon felt I; S2: The carbon felt I is immersed in a nickel nitrate solution with a concentration of 0.1 wt%, and then placed in an ultrasonic cleaner with a power of 1000 W for 15 min, and then dried in an oven at 150° C. for 2 h to obtain carbon felt II; S3: placing carbon felt II in a tubular furnace, setting the nitrogen flow rate to 200 ml / min, heating to 640°C, introducing hydrogen, setting the hydrogen flow rate to 150 ml / min, and keeping the temperature for 5 minutes to obtain carbon felt III; S4: stop introducing hydrogen, set the flow rate of propylene to 150 ml / min, the flow rate of nitrogen to 250 ml / min, keep warm at 640° C. for 15 min, and grow carbon nanotubes on the surface of carbon felt III by CVD method to obtain carbon felt IV; S5: Stop introducing propylene, introduce hydrogen chloride gas, set the hydrogen chloride flow rate to 200 ml / min, the nitrogen flow rate to 250 ml / min, purify the carbon felt IV at 1100° C. for 1 h, cool to room temperature, and obtain carbon felt for liquid flow battery.
[0047] Example 5 This example is carried out in a similar manner to that of Example 1, except that the 0.1 wt % nickel nitrate solution in step S2 is replaced with an equal volume of 1 wt % nickel nitrate solution to obtain carbon felt for liquid flow batteries.
[0048] Comparative Example 1 This comparative example is carried out in a similar manner to Example 1, except that the 68 wt % nitric acid solution in step S1 is replaced with an equal volume of 68 wt % sulfuric acid solution to obtain carbon felt for liquid flow battery.
[0049] Comparative Example 2 (Step S1 in Example 1 was omitted and activation treatment was not performed) S1: The untreated carbon felt I was immersed in a nickel nitrate solution with a concentration of 0.1wt%, and then placed in an ultrasonic cleaner with a power of 1000 W for 15 min, and then dried in an oven at 150°C for 2 h to obtain carbon felt II; S2: placing carbon felt II in a tubular furnace, setting the nitrogen flow rate to 200 ml / min, heating to 640°C, introducing hydrogen, setting the hydrogen flow rate to 150 ml / min, and keeping the temperature for 5 minutes to obtain carbon felt III; S3: stop introducing hydrogen, set the flow rate of propylene to 150 ml / min, the flow rate of nitrogen to 250 ml / min, keep warm at 640° C. for 15 min, grow carbon nanotubes on the surface of carbon felt III, and obtain carbon felt IV; S4: Stop introducing propylene, introduce hydrogen chloride gas, set its flow rate to 200 ml / min, purify the carbon felt IV at 1100° C. for 1 h, cool to room temperature, and obtain carbon felt for liquid flow battery.
[0050] Comparative Example 3 (Step S3 in Example 1 was omitted and no reduction treatment was performed) The untreated carbon felt is the same as that in Example 1.
[0051] Steps S1 and S2 are the same as those in Example 1 to obtain carbon felt II; S3: placing carbon felt II in a tube furnace, setting the flow rate of propylene to 150 ml / min and the flow rate of nitrogen to 250 ml / min, keeping the temperature at 640° C. for 15 min, growing carbon nanotubes on the surface of carbon felt III, and obtaining carbon felt IV; S4: Stop introducing propylene, introduce hydrogen chloride gas, set its flow rate to 200 ml / min, purify the carbon felt IV at 1100° C. for 1 h, cool to room temperature, and obtain carbon felt for liquid flow battery.
[0052] Comparative Example 4 This comparative example was carried out in a similar manner to Example 1, except that the carbon felt in Example 1 was replaced by untreated carbon felt II.
[0053] Untreated carbon felt II: It is made of asphalt-based fiber by needle punching method, with a size of 5×5×1 cm. The brand is asphalt-based cured carbon felt, and the manufacturer is Liaoning Jingu Carbon Materials Co., Ltd.
[0054] Test Case The specific surface area of the carbon felt for flow battery obtained in the above examples was tested, and the specific results are shown in Table 1.
[0055] In order to characterize the improvement of the composite carbon felt in battery performance, the untreated carbon felt I, untreated carbon felt II, and the carbon felt prepared for the flow battery in each example were used as the negative electrode of the battery, and the original carbon felt electrode was used as the positive electrode to assemble the all-vanadium flow battery for constant current charge and discharge test. The positive electrode electrolyte was 30 mL of 1.7 mol / L VO 2+ +3mol / LH 2 SO 4 Solution, the negative electrode electrolyte is 30mL of 1.7mol / LV 3+ +3mol / LH 2 SO 4 Solution. The performance data of each battery is shown in Table 1.
[0056] The present invention exemplarily provides that after the carbon felts provided in Examples 1 to 4 and the untreated carbon felt I are prepared into batteries, at a current density of 160 mA·cm -2 Schematic diagram of the Coulomb efficiency under Figure 4 ,As can be seen from the figure, the Coulomb efficiency of the composite carbon ,felt is significantly greater than that of the untreated carbon ,felt.
[0057] The present invention exemplarily provides that after the carbon felts provided in Examples 1 to 5 and Comparative Examples 1 to 4 are prepared into batteries, at a current density of 160 mA•cm -2 Schematic diagram of energy efficiency under Figure 5As can be seen from the figure, the energy efficiency of Examples 1 to 5 does not change substantially with the increase in the number of battery cycles, while the energy efficiency of Comparative Example 2 is significantly reduced after a long cycle, indicating that the carbon nanotubes of the carbon felt provided by the present invention are not easy to fall off.
[0058]
[0059] It can be seen from the above data that when the carbon felt provided by the present invention is used as an electrode material for a liquid flow battery, the coulombic efficiency, voltage efficiency and energy efficiency of the battery are significantly improved.
[0060] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing carbon felt for liquid flow battery, characterized in that: The method comprises the following steps: (1) activating the carbon felt in a concentrated nitric acid solution to obtain carbon felt I; the carbon felt is obtained by carbonizing polyacrylonitrile-based fibers; (2) immersing the carbon felt I in a transition metal salt solution, and then drying it to obtain carbon felt II; (3) subjecting the carbon felt II to a reduction treatment in the presence of hydrogen to obtain carbon felt III; (4) growing carbon nanotubes on the surface of carbon felt III by CVD method to obtain carbon felt IV; (5) The carbon felt IV is purified under a halogen atmosphere to obtain carbon felt for liquid flow battery.
2. The method for preparing a carbon felt for a liquid flow battery according to claim 1, characterized in that: The activation treatment conditions are: temperature of 50-70° C. and time of 20-40 min.
3. The method for preparing a carbon felt for a liquid flow battery according to claim 1 or 2, characterized in that: The transition metal salt solution is selected from at least one of a cobalt salt solution, an iron salt solution and a nickel salt solution; And / or, the concentration of the transition metal salt is 0.05-0.1 wt %.
4. The method for preparing a carbon felt for a liquid flow battery according to claim 1 or 2, characterized in that: The immersion is carried out under ultrasonic conditions, wherein the ultrasonic conditions are: power of 800-1200 W and time of 5-20 min.
5. The method for preparing a carbon felt for a liquid flow battery according to claim 1 or 2, characterized in that: The step (3), the step (4) and the step (5) are all carried out in an inert gas.
6. The method for preparing a carbon felt for a flow battery according to claim 5, characterized in that: The reduction treatment conditions are as follows: hydrogen flow rate is 150-250 ml / min, inert gas flow rate is 150-250 ml / min, temperature is 600-700° C., and time is 3-10 min.
7. The method for preparing carbon felt for liquid flow battery according to claim 5 or 6, characterized in that: The conditions of the CVD method are: growing carbon nanotubes on the surface of carbon felt III in the presence of organic hydrocarbon gas, with a flow rate of 150-300 ml / min for the organic hydrocarbon gas and 150-250 ml / min for the inert gas, a temperature of 600-700°C, and a time of 5-30 min.
8. The method for preparing carbon felt for liquid flow battery according to claim 5 or 6, characterized in that: The halogen atmosphere is selected from at least one of hydrogen chloride, chlorine and freon; And / or, the purification treatment conditions are: the flow ratio of the inert gas and the halogen atmosphere is (1-20):1, the temperature is 900-1500°C, and the time is 1-3h.
9. Carbon felt for liquid flow battery prepared by the method according to any one of claims 1 to 8.
10. Use of the carbon felt for liquid flow battery according to claim 9 in liquid flow battery.
Citation Information
Patent Citations
Preparation method of carbon felt for redox flow battery
CN115881981A
Cited By
Biomass derived carbon skeleton modified graphite felt electrode and preparation method and application thereof
CN122202346A